1942
DOI: 10.1136/bmj.1.4227.42
|View full text |Cite
|
Sign up to set email alerts
|

Sneezing, and Disinfection by Hypochlorites

Abstract: Illustrative Cases Case 1.-A lance-corporal was admitted with a history of injury to the right arm sustained by a fall while engaged in physical training. Clinically he showed a gross angtilation deformity of the mid-shaft of the right humerus, with shortening of one apd a half inches. Dorsiflexion of the wrist was not possible. One attempt at reduction had been made before admission. Treatment was carried out by the method described. At eight weeks clinic'al unin 'was sound, with steady improvement of the inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1943
1943
1958
1958

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…These calculated figures accord well with the figures obtained by Hare (1940), in direct observations of the expulsion of haemolytic streptococci in the mouth-spray of throat carriers; haemolytic streptococci were found to be contained in only a small proportion, from .0-3 to 3-5 %, of the expelled droplets, and, apparently, in none of the droplets small enough to form droplet-nuclei. namely, about 20,000 (Wells, 1935), about 100,000 (Bourdillon, et al 1942), and from 4500 to 150,000, on average 39,000 (Duguid, 1945). For a cough with the mouth initially closed, the calculated number of bacteria-carrying droplet-nuclei was 710; for speaking loudly one hundred words, it was 36.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These calculated figures accord well with the figures obtained by Hare (1940), in direct observations of the expulsion of haemolytic streptococci in the mouth-spray of throat carriers; haemolytic streptococci were found to be contained in only a small proportion, from .0-3 to 3-5 %, of the expelled droplets, and, apparently, in none of the droplets small enough to form droplet-nuclei. namely, about 20,000 (Wells, 1935), about 100,000 (Bourdillon, et al 1942), and from 4500 to 150,000, on average 39,000 (Duguid, 1945). For a cough with the mouth initially closed, the calculated number of bacteria-carrying droplet-nuclei was 710; for speaking loudly one hundred words, it was 36.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…for those of 17 ,. The persistence of aerial infection following sneezing has been studied by Bourdillon, Lidwell & Lovelock (1942); after a few sneezes in quick succession were performed in a small room, the air was examined at intervals with a slit sampler (Bourdillon, Lidwell & Thomas, 1941), an instrumerit which is probably the most convenient and efficient of the modem air-sampling devices. The number of bacteria-carrying droplet-nuclei which remained airborne after sneezing was found to decrease geometrically with time; only 4 % remained airborne after 30 min.…”
Section: Introductionmentioning
confidence: 99%
“…Air Sampling.-On four occasions during the winter, samples were collected from the air for bacteriological analysis with a slit-sampler modified from those described by Bourdillon et al (1948). Two different counts of airborne bacteria are recorded in the tables.…”
Section: Methodsmentioning
confidence: 99%
“…Hexylresorcinol was recommended for use as an air disinfectant by Twort and Baker (1942). Bourdillon et al (1948), in their comparative study of a variety of possible disinfectant agents, showed that as little as 2 ,Ag. per cu.…”
mentioning
confidence: 99%
“…We know something about the rate at which bacteria from mouth and nose are contributed to dust (Bourdillon, Lidwell & Lovelock, 1942;Hamburger, Green & Hamburger, 1945; Duguid, 1946;Dumbell, Lovelock & Lowbury, 1948). We also have information on the death-rate of such bacteria in dust under various environmental conditions (Cornet, 1889;Garrod, 1944; Lidwell & Lowbury, 1950).…”
mentioning
confidence: 99%